THE REGIONAL DIALECT CHANGE OF MAGETAN STUDENTS IN UNIVERSITAS BRAWIJAYA - PRIMARIDHA, ARGAYUDHA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: interference, dialect, lexical Language is important for human to deliver message and communicate insociety. There are hundreds languages in this world, one of them is Javanese.Javanese is a language with around 75.5 million users over the world. Those users spread over East Java, Central Java, Banten, Lampung, Riau, and included in some countries around the world such as Suriname, New Caledonia, Dutch, and west coast of Johor. Because of the big users of Javanese language, it shows many variations called dialect. There are three main dialects of Javanese, there are standard Javanese dialect, East Javanese dialect and Banyumas dialect. This study answers the following research problem. First, what are the lexical interferences of Magetan students in Malang, and the second what are the causes of dialect change by Magetan students in Malang.This study use qualitative approach. The data are utterances from conversation with the subject. The subjects of this study are Magetan students that studying in Brawijaya University. There are total three participants in this study. In analyzing the data, the writer uses Weinreich’s (1979) theory of lexicalinterference and individual factors of interference.The results of this study reveal that there are six lexical interferences of Magetan students in Malang. Those lexicons are mari, awakmu, kon, ndek, yo opo and arek. The factors of interference show there are different levels for each subject to accept lexical interference. This study also shows that interfered vocabulary is not always use by the subject.In conclusion, this study show there are lexical interference of Magetan students in Universitas Brawijaya and each subject has different level of interference. Finally after finishing this study, the writer hopes that there will be more students in Faculty of Cultural Studies use interference as focus of the study.